Energy market liberalisation in the FSU: Simulations with the GTAP model - Toni Riipinen (Bank of Finland, Institute for Economies in Transition (BOFIT), 2003)
This work considers effects of energy market liberalisation in the countries of the former Soviet Union (FSU).Our analysis is based on a computable general equilibrium (CGE) model called the Global Trade Analysis Project (GTAP).This specialised model makes it possible to evaluate effects in a general equilibrium set-up. Energy market reforms are widely discussed in the literature, but the use of CGE models has been limited.In the main part of the paper, we perform two experiments.The first is a benchmark liberalisation experiment in which all government taxes and subsidies are removed.The second is an attempt to simulate an increase in the export capacity of energy commodities into the European markets.In general, we find that liberalisation of FSU energy markets would increase welfare in the EU countries, while in the FSU welfare would decrease.This result is mainly due to the terms of trade effect, as export prices of FSU countries decrease.
URN:NBN:fi:bof-201408072017
Keywords: 330; energy; computable general equilibrium models; former Soviet Union; welfare analysis